Evaluating the waste and CO2 reduction potential of packaging by reuse model in supermarkets in Taiwan. (1st April 2023) - Lin, Hsin-Tien; Chiang, Cian-Wei; Cai, Jhao-Ning; Chang, Hsin-Yu; Ku, Yu-Nien; Schneider, Falk
Graphical abstract: Highlights: 50.8% of packaging waste and 59.8 % CO2 reduced in the reuse strategies proposed. Waste reduction is affected by consumers' adoption willingness of reuse strategies. Ambitious goals are suggested for fruits, eggs, and bottled water for retailers. Consumers' adoption willingness is proportional to regulations or the accessibility. Abstract: Consumption of single-use packaging has been increasing globally and the waste produced causes negative impacts on both human and the environment. Retailers, such as supermarkets, developed quickly in recent years to provide for the modern lifestyle, using a lot of packaging in the process of distribution and sales. This research evaluates the packaging waste and CO2 reduction potential of 10 different products sold in supermarkets in Taiwan when adopting different reuse strategies of Reduce, Return and Refill. In the suggested reuse strategies, a total of 8 kilotons of packaging waste and 30 kilotons of packaging CO2 can be reduced, accounting for 50.8% and 59.8% reduction of the current situation, respectively. Retailers are suggested to provide different reuse strategies and experiential activities to increase consumers familiarity with new consumption methods. Significant impacts are made with a slight change in the small proportion investigated, which suggests considerable benefits if the scope is expanded.